2012
DOI: 10.1100/2012/564939
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Administration of Tramadol after Elective Surgery Is as Effective as Intravenous Administration in Relieving Acute Pain and Inflammation in Dogs

Abstract: Subcutaneous (SC) administration of tramadol was compared with intravenous (IV) administration to evaluate analgesia following canine ovariohysterectomy (OHE). Healthy female dogs (n = 12) between 1 and 3 years of age (1.95 ± 0.65 years), weighing between 10.5 and 17.1 kg (13.12 ± 1.95 kg), were used. Pain was assessed at baseline before surgery and then hourly for 8 hr after surgery. Tramadol was administered both SC and IV at a dose of 3 mg/kg and provided significant postoperative analgesia, as indicated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Mechanical thresholds have been used in previous studies in animals [ 14 , 26 28 , 40 45 ] for the objective quantification of pain and to evaluate the analgesic efficacy of drugs. The analgesic effect of the test drug reported by these studies was either increase in the mechanical thresholds at the site of test compared to baseline [ 26 , 28 ] or concurrent rise in the mechanical thresholds equal to that produced by positive control analgesic or dose used to compare with [ 40 , 45 ] or equal rise in mechanical thresholds at the site of surgery by the same drug compared for two routes of administration [ 40 , 44 ]. Kukanich et al (2005) and Kaka et al (2015) reported increase in mechanical thresholds after administration of intravenous morphine at 1 mg/kg [ 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical thresholds have been used in previous studies in animals [ 14 , 26 28 , 40 45 ] for the objective quantification of pain and to evaluate the analgesic efficacy of drugs. The analgesic effect of the test drug reported by these studies was either increase in the mechanical thresholds at the site of test compared to baseline [ 26 , 28 ] or concurrent rise in the mechanical thresholds equal to that produced by positive control analgesic or dose used to compare with [ 40 , 45 ] or equal rise in mechanical thresholds at the site of surgery by the same drug compared for two routes of administration [ 40 , 44 ]. Kukanich et al (2005) and Kaka et al (2015) reported increase in mechanical thresholds after administration of intravenous morphine at 1 mg/kg [ 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EDTA vials were immediately processed for blood count (white and red blood cells, lymphocytes, neutrophils, monocytes, eosinophils, basophils) using an Exigo EOS bio 90 Boule Medical AB ® Analyser, while blood samples collected in the vials without an anticoagulant were centrifuged at 612 g for 10 min and serum samples were stored at −20 °C until analysis. β-endorphin concentrations were determined on the serum samples by a competitive inhibition enzyme immunoassay technique (CUSABIO ®) [44]. Once the reaction was stopped, the optical density of the plate (OD) was read using a Multiskan Go spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA), and Skanlt Software 4.1.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, subcutaneous TR has been demonstrated as an easy alternative to oral, intravenous, or intramuscular routes for postsurgical pain or local infiltrative analgesia. [39][40][41] Several studies have reported the development of new TR formulations such as hydroxypropyl methylcellulose tablets containing semipermeable membranes 42 and ethylcellulose microparticles 43 for oral route. Other examples include chitosan-based adhesives and carbohydrate hydrogels for skin delivery 44,45 and injectable polyhydroxybutyrate microspheres.…”
mentioning
confidence: 99%